Yield of transbronchial needle aspiration of mediastinal lymph nodes of 36 cases - Hala Mohamed Shalaby Samaha; Amro Abd Elhamid Moawad; Abdelhady Mohamed Shebl (Egyptian Journal of Chest Disease and Tuberculosis, 2015)
Background: Besides clarifying the etiology of unidentified lymphadenomegaly, puncturing hilar and mediastinal lymph nodes by a flexible bronchoscopic needle is an aid in diagnosing and staging bronchogenic cancer or other metastatic cancers and diagnosing other inflammatory diseases i.e. sarcoidosis tuberculosis. Objective: Our study had the principal objective to evaluate the positivity of transbronchial needle aspiration (TBNA). Method: We retrospectively reviewed 36 patients using bronchoscopy and histopathological reports and corresponding patients chart over 3 years from January, 2009 to December, 2012 at the department of chest disease at Mansoura University. Results: A total of 38 underwent FFB procedures. 2 (5%) patients were excluded due to incomplete follow up data. The yield of TBNA was positive in 22 patients (61%), of them 9 patients (25%) were positive for malignancy and 13 patients (36%) were diagnosed as inflammatory disease i.e. tuberculosis or sarcoidosis. Only 3 patients (8%) had documented bleeding after TBNA and, bleeding stopped spontaneously. No mortality was reported due to this procedure. Conclusion: Our study indicated that this method is safe, easy to perform, with a minimum of complications and useful for the diagnosis and staging of pulmonary neoplasms and mediastinal lymph node enlargement.